INOVASI TEKNOLOGI PEMBELAJARAN DENGAN MENGGUNAKAN APLIKASI KAHOOT DAN GOOGLE FORM PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Nikmawati Nikmawati (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2022)
This research aims to describe the effectiveness of using Kahoot and Google Form for the learning process. Google Form and Kahoot are used to make learning Islamic religious education more fun and not monotonous so that students don't get bored. Technological developments are increasingly rapid, especially in the field of education, so teachers are required to be able to innovate, such as by using technology as a learning media tool and as a learning evaluation tool. The research method used is descriptive qualitative by describing phenomena and existing literature. The results of the study show that Google Form and Kahoot have been successfully used as an alternative learning tool in the distance/online teaching and learning process and see the convenience provided by Kahoot and Google Form in the effectiveness of assessments for teachers, both in terms of time, energy and costs as well as convenience. For students to work on questions and be able to immediately see the results of their learning achievements, it is possible that Kahoot and Google Form can also be used as learning media that are very effective and efficient in the process of assessing student learning outcomes.